Chondral tumours: discrepancy rate between needle biopsy and surgical histology. - Oliveira, Ines; Chavda, Anesh; Rajakulasingam, Ramanan; Saifuddin, Asif (Skeletal Radiology, 2020)
Objective: To determine the reliability of image-guided core needle biopsy (IGCNB) for the diagnosis and grading of chondral tumours of bone compared with surgical histology.Materials and Methods: Retrospective review of patients with a chondral tumour of bone who underwent IGCNB and surgical resection between January 2007 and December 2017. Data collected included age, sex, skeletal location, technique used for IGCNB, IGCNB result including histological grade and comparison with surgical histology.Results: A total of 237 patients were included (135 males and 102 females with mean age 53.7 years, range 9-89 years). A total of 174 IGCNBs were CT-guided, 57 ultrasound-guided and 6 fluoroscopic-guided. Two hundred thirty-six of 237 (99.6%) IGCNBs were diagnostic for a chondral tumour, although grade could not be determined in 13 (5.5%) due to necrosis. A positive correlation for tumour grade between IGCNB and surgical histology was achieved in 181 cases (76.4%). In 36 patients (15.2%), IGCNB under-graded the tumour, while in 6 (2.5%), IGCNB over-graded the tumour. Discrepancy between IGCNB and surgical histology was significantly greater for surface/peripheral lesions (p = 0.02) and lesions arising from the flat bones or spine (p = 0.002).Discussion: IGCNB can achieve a diagnosis of a chondral tumour in a high proportion of cases when compared with final diagnosis from surgical resection specimens. However, correlation of tumour grade between IGCNB and resection histology is less reliable with discordance seen in almost one-quarter of cases, most commonly at non-appendicular sites. Therefore, IGCNB results should not be considered in isolation of imaging and clinical features when planning surgical management.